2020
DOI: 10.1002/chem.202001532
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Evidence of Spin‐Orbit Heavy Atom on the Light Atom 1H NMR Chemical Shifts Induced through H⋅⋅⋅I Hydrogen Bond

Abstract: Spin‐orbit (SO) heavy‐atom on the light‐atom (SO‐HALA) effect is the largest relativistic effect caused by a heavy atom on its light‐atom neighbors, leading, for example, to unexpected NMR chemical shifts of 1H, 13C, and 15N nuclei. In this study, a combined experimental and theoretical evidence for the SO‐HALA effect transmitted through hydrogen bond is presented. Solid‐state NMR data for a series of 4‐dimethylaminopyridine salts containing I−, Br− and Cl− counter ions were obtained experimentally and by theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…During the revision of this review, solid-state 1 H NMR and DFT study of a series of 4-(dimethylamino)­pyridinium with Cl, Br, and I counteranions has been reported . Discrepancy between the experimental and theoretical NMR shifts was attributed to an absence of the SO effects in the calculations of hydrogen-bonded ion pairs at the SR DFT level.…”
Section: Trends In So-hala Shifts Across the Periodic Tablementioning
confidence: 99%
“…During the revision of this review, solid-state 1 H NMR and DFT study of a series of 4-(dimethylamino)­pyridinium with Cl, Br, and I counteranions has been reported . Discrepancy between the experimental and theoretical NMR shifts was attributed to an absence of the SO effects in the calculations of hydrogen-bonded ion pairs at the SR DFT level.…”
Section: Trends In So-hala Shifts Across the Periodic Tablementioning
confidence: 99%
“…The electrons in the heavy iodine atom experience severe relativistic effects, and furthermore, halogens that are close to the nucleus of interest are known to increase the s -character of bonding orbitals of the respective nucleus thus evoking strong spin–orbit coupling effects. ,, This influence is generally known as heavy neighbor atom (HNA) effect. To allow for an unbiased statistical evaluation, these cases (outliers) are excluded from the statistics for SR approaches. The importance of explicit inclusion of spin–orbit effects for these compounds is demonstrated upon application of the SO-ZORA Hamiltonian (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, even such a light element like sulfur can induce an overall SO‐HALA shielding of −8 ppm at the bound 13 C nuclei . It has also been demonstrated that the SO‐HALA effect can be transmitted through hydrogen bonds …”
Section: Resultsmentioning
confidence: 99%